DAMPAK KEBIJAKAN DIVIDEN PADA PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PERBANKAN DI BURSA EFEK - Efendi, Idris; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the effect of dividend policy on the influence of financial performance to the firm value.The population is the entire companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been carried out by using purposive sampling and based on the determined criteria there are 7 samples of banking company which are consecutively active in the capital market activity, and they do not experience any loss and share their dividend during the years of 2009-2013. The research data is the secondary data which has been obtained from Indonesia Stock Exchange (www.idx.co.id. The multiple linear regerssions analysis technique with the SPSS (Statistical Product and Service Solutions) application is used as the research hypothesis test. The result of hypothesis test describes that: 1) Liquidity has significant influence to the firm value. 2) Leverage variable does not have any influence to the firm value. 3) profitability variable has significant influence to the firm value. 4) dividend policy does not have any effect on the influence of liquidity to the value. 5) dividend policy does not have any effect to the influence of leverage to the firm value. 6) dividend policy does not have any effect to profitability influence to the firm value.Keywords: Liquidity, Leverage, Profitability, Firm Value, and Dividend Policy